Difference between revisions of "1993 AIME Problems/Problem 5"
(solution) |
(→Solution 3 (Overkill)) |
||
(15 intermediate revisions by 5 users not shown) | |||
Line 1: | Line 1: | ||
== Problem == | == Problem == | ||
− | Let <math>P_0(x) = x^3 + 313x^2 - 77x - 8\,</math>. For [[integer]]s <math>n \ge 1\,</math>, define <math>P_n(x) = P_{n - 1}(x - n)\,</math>. What is the [[coefficient]] of <math>x\,</math> in <math>P_{20}(x)\,</math>? | + | <!-- don't remove the following tag, for PoTW on the Wiki front page--><onlyinclude>Let <math>P_0(x) = x^3 + 313x^2 - 77x - 8\,</math>. For [[integer]]s <math>n \ge 1\,</math>, define <math>P_n(x) = P_{n - 1}(x - n)\,</math>. What is the [[coefficient]] of <math>x\,</math> in <math>P_{20}(x)\,</math>?<!-- don't remove the following tag, for PoTW on the Wiki front page--></onlyinclude> |
− | == Solution == | + | == Solution 1 == |
− | Notice that < | + | Notice that |
+ | <cmath>\begin{align*}P_{20}(x) &= P_{19}(x - 20)\\ &= P_{18}((x - 20) - 19)\\ &= P_{17}(((x - 20) - 19) - 18)\\ &= \cdots\\ &= P_0(x - (20 + 19 + 18 + \ldots + 2 + 1)).\end{align*}</cmath> | ||
− | + | ||
+ | Using the formula for the sum of the first <math>n</math> numbers, <math>1 + 2 + \cdots + 20 = \frac{20(20+1)}{2} = 210</math>. Therefore, <cmath>P_{20}(x) = P_0(x - 210).</cmath> | ||
+ | |||
+ | Substituting <math>x - 210</math> into the function definition, we get <math>P_0(x-210) = (x - 210)^3 + 313(x - 210)^2 - 77(x - 210) - 8</math>. We only need the coefficients of the linear terms, which we can find by the [[binomial theorem]]. | ||
+ | *<math>(x-210)^3</math> will have a linear term of <math>{3\choose1}210^2x = 630 \cdot 210x</math>. | ||
+ | *<math>313(x-210)^2</math> will have a linear term of <math>-313 \cdot {2\choose1}210x = -626 \cdot 210x</math>. | ||
+ | *<math>-77(x-210)</math> will have a linear term of <math>-77x</math>. | ||
+ | Adding up the coefficients, we get <math>630 \cdot 210 - 626 \cdot 210 - 77 = \boxed{763}</math>. | ||
+ | |||
+ | == Solution 2 == | ||
+ | Notice the transformation of <math>P_{n-1}(x)\to P_n(x)</math> adds <math>n</math> to the roots. Thus, all these transformations will take the roots and add <math>1+2+\cdots+20=210</math> to them. (Indeed, this is very easy to check in general.) | ||
+ | |||
+ | Let the roots be <math>r_1,r_2,r_3.</math> Then <math>P_{20}(x)=(x-r_1-210)(x-r_2-210)(x-r_3-210).</math> By Vieta's/expanding/common sense, you see the coefficient of <math>x</math> is <math>(r_1+210)(r_2+210)+(r_2+210)(r_3+210)+(r_3+210)(r_1+210).</math> Expanding yields <math>r_1r_2+r_2r_3+r_3r_1+210\cdot 2(r_1+r_2+r_3)+3\cdot 210^2.</math> Using Vieta's (again) and plugging stuff in yields <math>-77+210\cdot 2\cdot -313+3\cdot 210^2=\boxed{763}.</math> | ||
+ | |||
+ | == Solution 3 (Overkill) == | ||
+ | Denote the coefficient of term <math>x^m</math> of polynomial <math>P_n(x)</math> as <math>c_{m, n}</math>. We can see that <math>c_{2, 0} = 313</math>, <math>c_{1, 0} = -77</math>, and <math>c_{0, 0} = -8</math>. Note that <math>(x-n)^3 = x^3-3nx^2+3n^2x-n^3</math> and <math>(x-n)^2 = x^2-2nx+n^2</math> | ||
+ | When substituting <math>x-1</math> for <math>x</math> in <math>P_0(x)</math>, we get that <math>P_1(x) = P_0(x-1) = (x^3-3x^2+3x-1) + 313(x^2-2x+1) -77(x-1) -8</math>. Observe that | ||
+ | <cmath>c_{2,1} = c_{2,0} - 3(1) = 313 - 3 = 310</cmath> | ||
+ | It is evident that | ||
+ | <cmath>c_{2,n} = c_{2,n-1} - 3n</cmath> | ||
+ | Define the generating function <math>C_2(X)</math> as | ||
+ | <cmath>C_2(X) := \sum_{n \geq 0} c_{2,n}X^n</cmath> | ||
+ | By multiplying both sides of the previous recurrence relation and taking the sum of the terms <math>\forall n\geq 1</math>, we get that | ||
+ | <cmath>\implies \sum_{n\geq1} c_{2,n}X^n = \sum_{n\geq1}c_{2,n-1}X^n + 3\sum_{n\geq1}nX^n</cmath> | ||
+ | <cmath>\implies \sum_{n\geq0} c_{2,n}X^n - c_{2,0} = X\sum_{n\geq0}c_{2,n}X^n + 3\sum_{n\geq1}nX^n</cmath> | ||
+ | <cmath>\implies C_2(X) - 313 = XC_2(X) + 3\cdot \frac{X}{(1-X)^2}^*</cmath> | ||
+ | <cmath>\implies C_2(X) = \frac{313}{1-X} - \frac{3X}{(1-X)^3}</cmath> | ||
+ | <cmath>= \frac{313X^2 - 629X + 313}{(1-X)^3} = (313X^2 - 629X + 313) \cdot \sum_{n\geq0}{n+2 \choose 2}X^n\ ^\dagger</cmath> | ||
+ | <cmath>\implies c_{2,n} = 313{n+2 \choose 2} - 629{n+1 \choose 2} + 313{n \choose 2}^\ddagger = \frac{-3n^2 - 3n + 626}{2}</cmath> | ||
+ | We can perform a similar analysis on <math>c_{1,n}</math> to get the recurrence relation | ||
+ | <cmath>c_{1,n} = c_{1, n-1} + c_{2,n-1}\cdot(-2n) + 3n^2</cmath> | ||
+ | <cmath>= c_{1, n-1} +3n^3 - 626n</cmath> | ||
+ | Define the generating function <math>C_1(X)</math> as | ||
+ | <cmath>C_1(X) := \sum_{n\geq0}c_{1,n}X^n</cmath> | ||
+ | We can then perform this process again on our new recurrence relation: | ||
+ | <cmath>\implies \sum_{n\geq1} c_{1,n}X^n = \sum_{n\geq1}c_{1,n-1}X^n + 3\sum_{n\geq1}n^3X^n - 626\sum_{n\geq1}nX^n</cmath> | ||
+ | <cmath>\implies \sum_{n\geq0} c_{1,n}X^n - c_{1,0} = X\sum_{n\geq0}c_{1,n}X^n + 3\sum_{n\geq1}n^3X^n - 626\sum_{n\geq1}nX^n</cmath> | ||
+ | <cmath>\implies C_1(X) + 77 = XC_1(X) + 3\cdot \frac{X(X^2+4X+1)}{(1-X)^4} - 626\cdot \frac{X}{(1-X)^2}</cmath> | ||
+ | <cmath>\implies C_1(X) = \frac{-77(1-X)^4 + 3X(X^2+4X+1) - 626X(1-X)^2}{(1-X)^5}</cmath> | ||
+ | <cmath>= \frac{-77X^4-315X^3+802X^2-315X-77}{(1-X)^5} </cmath> | ||
+ | <cmath>=(-77X^4-315X^3+802X^2-315X-77) \cdot \sum_{n\geq0}{n+5 \choose 5}X^n</cmath> | ||
+ | <cmath>\implies c_{1,n} = -77{n+4 \choose 4} - 315{n+3 \choose 4} + 802{n+2 \choose 4} - 315{n+1 \choose 4} -77{n \choose 4}</cmath> | ||
+ | <cmath>= \frac{3n^4+6n^3-1249n^2-1252n-308}{4}</cmath> | ||
+ | Finally, we can plug <math>n=20</math> into our new explicit formula to get <cmath>c_{1,20} = \boxed{763}</cmath> | ||
+ | <math>^*</math>This can be calculated by differentiating the generating function of the sequence 1, 1, 1, ... <math>(\sum_{n\geq0}X^n)</math> and multiplying by <math>X</math>. | ||
+ | |||
+ | <math>^\dagger</math>This form can be found by applying Newton's generalized binomial theorem. | ||
+ | |||
+ | <math>^\ddagger</math>This formula can be found by convolving the polynomial with the series. | ||
+ | |||
+ | - MathCactus0_0 (don't try this on a test unless you can't think of anything else!!!) | ||
== See also == | == See also == | ||
Line 11: | Line 62: | ||
[[Category:Intermediate Algebra Problems]] | [[Category:Intermediate Algebra Problems]] | ||
+ | {{MAA Notice}} |
Latest revision as of 12:17, 16 September 2024
Problem
Let . For integers , define . What is the coefficient of in ?
Solution 1
Notice that
Using the formula for the sum of the first numbers, . Therefore,
Substituting into the function definition, we get . We only need the coefficients of the linear terms, which we can find by the binomial theorem.
- will have a linear term of .
- will have a linear term of .
- will have a linear term of .
Adding up the coefficients, we get .
Solution 2
Notice the transformation of adds to the roots. Thus, all these transformations will take the roots and add to them. (Indeed, this is very easy to check in general.)
Let the roots be Then By Vieta's/expanding/common sense, you see the coefficient of is Expanding yields Using Vieta's (again) and plugging stuff in yields
Solution 3 (Overkill)
Denote the coefficient of term of polynomial as . We can see that , , and . Note that and When substituting for in , we get that . Observe that It is evident that Define the generating function as By multiplying both sides of the previous recurrence relation and taking the sum of the terms , we get that We can perform a similar analysis on to get the recurrence relation Define the generating function as We can then perform this process again on our new recurrence relation: Finally, we can plug into our new explicit formula to get This can be calculated by differentiating the generating function of the sequence 1, 1, 1, ... and multiplying by .
This form can be found by applying Newton's generalized binomial theorem.
This formula can be found by convolving the polynomial with the series.
- MathCactus0_0 (don't try this on a test unless you can't think of anything else!!!)
See also
1993 AIME (Problems • Answer Key • Resources) | ||
Preceded by Problem 4 |
Followed by Problem 6 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.